Screening of Anticandidal and Antidermatophytic activities of Gracilaria edulis and Gracilaria verrucosa (Rhodophyceae) from the Gulf of Mannar, Manappad Coast, Tamilnadu - Venugopalan Venkatesalu, Gnanaprakasam A. Raj, M. Chandrasekaran Sakthivel Jegan (Journal of Biomedical and Pharmaceutical Research, 2016)
The present studies five different solvents of viz., hexane, chloroform, ethyl acetate, acetone and methanol extracts of Gracilaria edulis (S.G. Gemelin) P .C. Silva and Gracilaria verrucosa (Huds.) Papenfuss, were collected from Manappad, Gulf of mannar Biosphere, Reserve, Tamilnadu, India. Their crude extracts were tested against six yeast viz., Candida albicans, C. krusei, C. guilliermondi, C. parapsilosis, C. tropicalis and C. glabrata. Four dermatophytes viz., Trichophyton rubrum, T. mentagrophytes, Microsporum gypseum and Epidermophyton flocossum were determined. Among the highest antifungal activity was recorded in the ethyl acetate extract of G. edulis than the other extracts. The mean zone of inhibition produced by the extracts in disc diffusion assays against the tested fungal strains ranged from 7.0 to 14.5 mm and the lowest MIC (250 µg/ml) and MFC (500 µg/ml). The ethyl acetate extracts of the seaweeds showed the strong phytochemicals, terpenoids, tannins, phenolic compounds and steroids in G. edulis and G. verrucosa than the other solvents extracts. The results obtained in the present study suggest that ethyl acetate extracts of G. edulis and G. verrucosa can be used in treating disease caused by C. parapsilosis, C. albicans and T. rubrum. Key words: Gracilaria edulis, Gracilaria verrucosa, Antifungal activity and phytochemical analyses